9x-12=-60

Simple and best practice solution for 9x-12=-60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-12=-60 equation:


Simplifying
9x + -12 = -60

Reorder the terms:
-12 + 9x = -60

Solving
-12 + 9x = -60

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 9x = -60 + 12

Combine like terms: -12 + 12 = 0
0 + 9x = -60 + 12
9x = -60 + 12

Combine like terms: -60 + 12 = -48
9x = -48

Divide each side by '9'.
x = -5.333333333

Simplifying
x = -5.333333333

See similar equations:

| 1-2=43 | | 16r^2s^2= | | 1/2x=7.5 | | -8w-8=-7w | | 3y+4x+18=44 | | 3y=5y+9 | | 3x+2=3x+50 | | x-18/24=4/1.4 | | nm=10 | | 27/32•4/9 | | 4-n/6=3 | | 1/2x-4=14 | | 9r-2s-3rt+7s= | | (2x^2y)(-3x^2y^3)=0 | | (2x^2y)(-3x^2y^3)= | | 2q=-10+4q | | 7b+3a+5-7-2b= | | w=1/2l | | -7-7v=3v+84 | | 120x^2+5x=0 | | 5-4+7x+1=9x+9 | | -41/x−17/x=-39 | | [(4-8)x2-10]/2 | | -66-5n=6+7n | | .4(3x-20)+.6=x+3.8 | | 5-4+7x+1=0x+1 | | 22x+23= | | -39/x−26/x=-46 | | -4x+x-1=0 | | 2x+(3x+50)=180 | | -7-7v=3v+48 | | 9j=-8+10j |

Equations solver categories